Effect of Garlic in ration on immune response of broiler chicken - Shalash, Ali A.H.; Al-Ibadi, Israa N. A. (The Iraqi Journal of Veterinary Medicine, 2003)
This study was conducted to investigate the effect of two levels of garlic supplementation to broiler ration on immune response to Newcastle and Gumboro vaccines. A total of 120 chick of broiler breeder males faobro strain were used at one day old. The birds at seven days old were divided into three groups. Each group was consisted of fourty birds. The first group (T1) was treated with garlic at 1% ratio. The second group (T2) was treated with garlic at 2% ratio , while control group (C) was not given garlic with ration. The birds were immunized after decline of Maternal Antibodies of Newcastle and Gumboro until (34) days old. The first vaccine occurred at 35 day old with combined vaccine of Newcastle lasota -C30 strain and Gumoro Lukert strain, second vaccine was done after ten days from the first vaccine. The titer of haemagglutination inhibition antibodies of Newcastle vaccine, titer of Gumboro precipitating antibodies and the titer of antibodies in ELISA test to these vaccine were measured after ten days of each vaccine, and the results were as follows: -The titer of haemagglutinating inhibiting antibodies of Newcastle vaccine was increased significantly in Tl and T2 groups (P < 0.05) compared with control group. -The titer of Gumboro precipitating antibodies was increased significantly in Ti and T2 groups (P < 0.05) compared with control group after second vaccine only. -ELISA test results indicated a significant increase in titer of antibodies of Newcastle and Gumboro vaccines (P <0.05) compared with control group.